Epidemiology and Hemato-Biochemical Changes in Mange Infested Goats - Shah, Kuntal S.; Mandali, Ghanshyam C.; Rao, Neha; Patel, Ashish C.; Panchal, Ronak P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Mange in goats is a contagious skin disease characterized by crusty, pruritic dermatitis and patchy/generalized alopecia. It is caused by a variety of parasitic mites burrowing in or living on the skin. For the present study, 30 mange-infested goats of Surti and Marwari breeds were selected from those presented at the Veterinary Clinical Complex of the College and from surrounding villages of Anand, and six goats from the University farm were taken as a healthy control group. The maximum prevalence of sarcoptic mange was found in the age group of 1-2 years of age (60.00%), followed by >2 years (26.67%) and <1 year (13.33%) age groups, and also in females than the males (76.67% vs. 23.33%). Hematological examinations revealed that the mean (±SE) values haemoglobin, total erythrocyte count, total platelet count, pack cell volume, neutrophils, and monocytes were decreased significantly (p <0.01), whereas total leucocyte count, lymphocytes and eosinophils were increased significantly (p <0.01) in mange affected goats in comparison to healthy goats. The serum biochemical examinations revealed that the mean (±SE) values of alanine aminotransferase activity, total protein, zinc, and copper were significantly decreased (p <0.01). In contrast, aspartate aminotransferase activity was non significantly increased (p <0.01) in mangy goats, and no significant difference (p >0.01) was found in values of creatinine when compared with healthy goats.